Where, When and With Whom: Cannabis Use, Settings and Self-Regulation Rules. (September 2021) - Skliamis, Kostas; Benschop, Annemieke; Liebregts, Nienke; Korf, Dirk J.
This article examines to what extent and how cannabis users in different countries, with different cannabis legislation and policies practice normalization and self-regulation of cannabis use in everyday life. Data were collected in a survey among a convenience sample of 1, 225 last-year cannabis users aged 18–40 from seven European countries, with cannabis policies ranging from relatively liberal to more punitive. Participants were recruited in or in the vicinity of Dutch coffeeshops. We assessed whether cannabis users experience and interpret formal control and informal social norms differently across countries with different cannabis policies. The findings suggest that many cannabis users set boundaries to control their use. Irrespective of national cannabis policy, using cannabis in private settings and setting risk avoidance rules were equally predominant in all countries. This illustrates that many cannabis users are concerned with responsible use, demonstrating the importance that they attach to discretion. Overall, self-regulation was highest in the most liberal country (the Netherlands). This indicates that liberalization does not automatically lead to chaotic or otherwise problematic use as critics of the policy have predicted, as the diminishing of formal control (law enforcement) is accompanied by increased importance of informal norms and stronger self-regulation. In understanding risk-management, societal tolerance of cannabis use seems more important than cross-national differences in cannabis policy. The setting of cannabis use and self-regulation rules were strongly associated with frequency of use. Daily users were less selective in choosing settings of use and less strict in self-regulation rules. Further differences in age, gender, and household status underline the relevance of a differentiated, more nuanced understanding of cannabis normalization.